2020
DOI: 10.3390/ijerph17072500
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Geochemical Controls of Arsenic and Uranium in Groundwater-Derived Drinking Water in Bihar, India

Abstract: Chronic exposure to groundwater containing elevated concentrations of geogenic contaminants such as arsenic (As) and uranium (U) can lead to detrimental health impacts. In this study, we have undertaken a groundwater survey of representative sites across all districts of the State of Bihar, in the Middle Gangetic Plain of north-eastern India. The aim is to characterize the inorganic major and trace element aqueous geochemistry in groundwater sources widely used for drinking in Bihar, with a particular focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 136 publications
3
16
0
Order By: Relevance
“…However, the prevailing oxic and alkaline conditions and carbonate complexation with U (VI) in the lower catchment zone can facilitate U mobilisation (Barnett et al, 2002;, and results in significantly higher U concentrations in the lower catchment compared to the other two catchment zones. These concentrations are comparable with concentrations found by Richards et al (2020), but are not as high as those detected by Lapworth et al (2017) and Coyte et al (2019) in north-west India, but aquifer redox conditions are comparable and concentrations are approaching the WHO guideline value of 30 g/L.…”
Section: Groundwater Quality Constraints and Controlssupporting
confidence: 76%
See 1 more Smart Citation
“…However, the prevailing oxic and alkaline conditions and carbonate complexation with U (VI) in the lower catchment zone can facilitate U mobilisation (Barnett et al, 2002;, and results in significantly higher U concentrations in the lower catchment compared to the other two catchment zones. These concentrations are comparable with concentrations found by Richards et al (2020), but are not as high as those detected by Lapworth et al (2017) and Coyte et al (2019) in north-west India, but aquifer redox conditions are comparable and concentrations are approaching the WHO guideline value of 30 g/L.…”
Section: Groundwater Quality Constraints and Controlssupporting
confidence: 76%
“…These exceedances were only found in the upper and mid catchment, and are linked to reducing conditions in the shallow aquifer, which facilitate the reductive dissolution of iron oxyhydroxides and the release of bound arsenic (e.g. Nickson et al, 2000;BGS/DHPE 2001;Richards et al, 2020). Shallow DOC concentrations were comparable for all three catchment zones (range 0.5-2.5 mg/L), but lower concentrations (c.0.5 mg/L) are found at depth in the Pleistocene deposits across the catchment.…”
Section: Groundwater Quality Constraints and Controlsmentioning
confidence: 99%
“…It has been reported that the U content is high in metamorphic rocks of granite origin, acidic igneous rocks, shale, and carbonate minerals [10]. The high U concentration is associated with HCO 3 − , NO 3 − , and oxic conditions rather than acidic or anoxic conditions [11]. The major species under oxidation conditions in groundwater is U(VI) in the UO 2 2+ form, which makes neutral complexes with high mobility.…”
Section: Introductionmentioning
confidence: 99%
“…U(IV) and U(V) predominate in anaerobic conditions. U(IV) has a strong precipitation trend similar to uraninite, but the U(V) species form soluble complexes [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] In the recent times, due to geogenic cause, the arsenic poisoning in ground water has increased many folds in the state of Bihar in endemic proportions. [14][15][16][17][18] This has increased the disease burden in the arsenic exposed population of Bihar. Arsenic poisoning leading to cancer has been studied globally, and a relationship between arsenic and cancer has been established.…”
Section: Introductionmentioning
confidence: 99%